2015
DOI: 10.1109/toh.2014.2384049
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Haptic Interaction Patterns in Dyadic Joint Object Manipulation

Abstract: The development of robots that can physically cooperate with humans has attained interest in the last decades. Obviously, this effort requires a deep understanding of the intrinsic properties of interaction. Up to now, many researchers have focused on inferring human intents in terms of intermediate or terminal goals in physical tasks. On the other hand, working side by side with people, an autonomous robot additionally needs to come up with in-depth information about underlying haptic interaction patterns tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 29 publications
2
55
1
Order By: Relevance
“…The objective of studying the way humans cooperate in co-manipulation situations is to be able to replicate these behaviors, or at least understand them well enough to help robots adapt to humans. Reed et al [4] demonstrated that in one degree-of-freedom pointing tasks, humans dyads performed better than individuals, result confirmed in several other studies [5] [6] [7] [8]. They also observed that replicating human behavior could be easily done and can reduce the perceived difference between a human partner and a robotic partner.…”
Section: Introductionmentioning
confidence: 65%
“…The objective of studying the way humans cooperate in co-manipulation situations is to be able to replicate these behaviors, or at least understand them well enough to help robots adapt to humans. Reed et al [4] demonstrated that in one degree-of-freedom pointing tasks, humans dyads performed better than individuals, result confirmed in several other studies [5] [6] [7] [8]. They also observed that replicating human behavior could be easily done and can reduce the perceived difference between a human partner and a robotic partner.…”
Section: Introductionmentioning
confidence: 65%
“…Some research involved shared virtual-environment loads [23], [24], and others involved upper arm movements of individuals and dyads [25], [18]. These experiments clarify many aspects of pHRI, including verifying that haptic information aids in co-manipulation tasks, noting some interaction patterns, and combining planning and learning to complete goal-oriented tasks.…”
Section: B Intent and Haptic Informationmentioning
confidence: 93%
“…There are several metrics used to assess the effectiveness of human-robot interactions [10], [11]. In [10] authors present analysis of humanrobot co-operative load transport to adjust the robot's urge to complete the task based on the human feedback.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the authors introduce metrics that quantify mass and grasp. Moreover, the study to understand the interaction patterns involving two or more humans in the physical task, a confusion matrix was used to classify some behavioural patterns [11]. Studies done in morphological computation [12] show that perception and action are related through a shared embodiment [13], [14].…”
Section: Introductionmentioning
confidence: 99%